2017
DOI: 10.1186/s12864-017-3788-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate transmission-blocking antigen genes in Theileria annulata and related vector-borne apicomplexan parasites

Abstract: BackgroundVector-borne apicomplexan parasites are a major cause of mortality and morbidity to humans and livestock globally. The most important disease syndromes caused by these parasites are malaria, babesiosis and theileriosis. Strategies for control often target parasite stages in the mammalian host that cause disease, but this can result in reservoir infections that promote pathogen transmission and generate economic loss. Optimal control strategies should protect against clinical disease, block transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…It is generally assumed that sexual commitment of Theileria is identical to Babesia and gametocytes occur in the circulating blood (Mehlhorn and Shein, 1984 ; Mehlhorn and Schein, 1993 ; Zapf and Schein, 1994b ; Gauer et al, 1995 ; Shaw, 2003 ; Bishop et al, 2004 ; Uilenberg, 2006 ). This is supported by recent descriptions of genes with expression specific to sexual commitment in intra-erythrocytic stages of Theileria sensu stricto species (Pieszko et al, 2015 ; Lempereur et al, 2017 ) and T. equi (Bastos et al, 2013 ). The gametocytes are taken up into the tick midgut together with the blood meal.…”
Section: Gamogony: Sexual Reproduction In the Gut Of The Tick Vectorsupporting
confidence: 52%
“…It is generally assumed that sexual commitment of Theileria is identical to Babesia and gametocytes occur in the circulating blood (Mehlhorn and Shein, 1984 ; Mehlhorn and Schein, 1993 ; Zapf and Schein, 1994b ; Gauer et al, 1995 ; Shaw, 2003 ; Bishop et al, 2004 ; Uilenberg, 2006 ). This is supported by recent descriptions of genes with expression specific to sexual commitment in intra-erythrocytic stages of Theileria sensu stricto species (Pieszko et al, 2015 ; Lempereur et al, 2017 ) and T. equi (Bastos et al, 2013 ). The gametocytes are taken up into the tick midgut together with the blood meal.…”
Section: Gamogony: Sexual Reproduction In the Gut Of The Tick Vectorsupporting
confidence: 52%
“…Moreover, metagenomic sequencing enables reanalysis of sequence data for new resistance genes discovered after the samples were initially analyzed [ 51 , 52 ], enabling retrospective analysis of monitoring data. An additional benefit of utilizing metagenomic sequencing over qPCR arrays is the possibility to computationally predict novel resistance genes from sequence data [ 53 , 54 ], although this specific practice is quite unlikely to be employed as part of monitoring schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study used in silico analysis combined with gene expression in tick stages of the parasite to identify T. annulata candidate antigens for a transmissionblocking vaccine. By searching the T. annulata genome for amino acid domains on similar transmission-blocking sexual-stage targets from Plasmodium and Babesia parasites, this study identified candidates encoding the 6-cys and cysteine-rich domain protein families [39]. Vaccine trials in cattle are needed to test these newly identified vaccine candidates in their efficiency to block T. annulata transmission.…”
Section: Vaccines Against Theileria Spp Of Importance To Cattlementioning
confidence: 99%
“…and Theileria spp. [39,101,105,106] and have been shown to be effective in reducing transmission upon vaccination in different models [107]. Antigens differentially expressed in kinete stages are also possible candidates for developing TBV.…”
Section: Vaccines Against Bovine Babesiosismentioning
confidence: 99%